Comparison of the effectiveness and renal safety of tenofovir versus entecavir in patients with chronic hepatitis B - Beatriz López Centeno; Roberto Collado Borrell; Montserrat Pérez Encinas; Maria Luisa Gutiérrez García; Patricia Sanmartin Fenollera (Farmacia Hospitalaria, 2016)
Objective: To compare the effectiveness and renal safety of treatment with tenofovir versus entecavir in patients with chronic hepatitis-B. Methods: Retrospective study in hepatitis-B patients who initiated treatment with tenofovir or entecavir since January 1998 until 2013. The primary effectiveness variable was defined as viral DNA < 20 UI/ml (HBV-DNA) and the variable for renal safety was variations in glomerular filtration rate (eGFR) after 48 weeks of treatment. Results: The analysis was conducted in 64 patients (1:1), with similar characteristics except for the prevalence of naive patients (p=0.036), comorbidities (p=0.077) and nephrotoxic drugs (p=0.088) in the entecavi arm, while the tenofovir arm presented a prevalence of patients with HBV-DNA < 20 UI/ml (p=0.032) and HBeAg-positive (p=0.050). Statistical univariate analysis and adjustment for confounding variables was conducted through the Propensity Score (PS). The outcomes for the primary effectiveness variable showed tenofovir superiority after PS adjustment, with an ORadj=6.7 (95% CI:1.2-35.3; p=0.028). Three patients on tenofovir experienced seroconversion (p=0.148). The outcomes for the primary safety variable (eGFR < 60 ml/min/1.73m2) showed no difference between both arms after adjustment, achieving an ORadj=0.6 (95% CI:0.1-2.8; p=0.521). The tenofovir arm registered two cases of treatment interruption due to renal toxicity, with subsequent recovery, including one Fanconi Syndrome. Conclusions: In our study, there are significant differences between both treatments regarding effectiveness, with tenofovir demonstrating superiority. In terms of renal safety, we have not found any significant differences, but two cases of treatment interruption due to renal toxicity with tenofovir lead us to the conclusion that treatment decision in patients with renal function alteration should include an individualized assessment of each case.